One Voice: The Strength of Harmonious Singularity. Issue 174 (16th March 2021) - Lewis, Rob
Abstract : Rob Lewis currently serves as Executive Director of Youth Headquarters in Red Deer, Alberta, Canada. He has a diploma in theology from Vanguard College, Edmonton, Alberta, and is certified in Policy Governance proficiency. In this article, he investigates the challenges and benefits of the board's use of One Voice in communicating their direction concisely and effectively with their staff team .